Experiment and simulation research of storage for small grain steel silo - Ledao, zhang; Xi, Chen; Hang, Liu; Wei, Peng; Zhongjie, Zhang; Guangyue, Ren (International Journal of Agricultural and Biological Engineering, 2016)
Knowing the temperature distribution in silo is a convenient and efficient way to control the process of grain storage. A three-dimensional (3-D) numerical model was used to study the temperature variation in small grain steel silo under quasi-steady state. In this study, experiments were conducted and porous media model was adopted. Results of numerical simulation and experiment were compared and the results indicated that grain temperature was influenced by temperature of the wall, grain stacking height, and the distance between grain and wall. The higher the wall temperature, the more the temperature increases. If the wall temperature is low, the effect of wall temperature on temperature distribution is significant. The temperature at the top part of grain varied obviously with the changes of temperature in air layer. Overall, numerical simulation results coincided with experimental results and the model established in this study is valuable for predicting grain temperature in steel silo. Keywords: small grain steel silo, quasi-steady state storage, numerical simulation, porous media model, grain storage DOI: 10.3965/j.ijabe.20160903.1946 Citation: Zhang L D, Chen X, Liu H, Peng W, Zhang Z J, Ren G Y. Experiment and simulation research of storage for small grain steel silo. Int J Agric & Biol Eng, 2016; 9(3): 170－178.